Pembimbingan Kegiatan Kampus Mengajar 6 dengan Program Peningkatan Kemampuan Literasi dan Numerasi Siswa SMPN 1 Turikale dan SD Inpres 5/81 Passippo - Muhammad Akil; Aulia Sabril; Faisal Najamuddin; Labusab Labusab; Ahmad Risal (PT. Global Research Collaboration, 2024)
Elementary school has a crucial role in forming students' literacy and numeracy skills, which are the foundation for learning at higher levels of education. Various studies show that literacy and numeracy levels among students still require serious attention. The Teaching Campus Program, as part of the Merdeka Belajar – Kampus Merdeka (MBKM) initiative, is here to answer this challenge by involving students in efforts to improve the quality of education in primary and secondary schools in Indonesia. The Teaching Campus 6 program focuses on improving the literacy and numeracy skills of students at SMPN 1 Turikale and SD Inpres 5/81 Passippo. Activities will be carried out from July-December 2023 with the target participants being all students in grades 1-6 in Presidential Instruction 5/81 Passippo and specifically grades 8 at junior high school level. The implementation of this program is carried out through 5 stages, namely orientation and introduction of students to the Field Supervisor, explanation of KM6 activities, coordination with the district office and school principal, presentation of the work program and monitoring and evaluation. Campus teaching activities prove the importance of direct interaction between supervisor and students. This allows for the exchange of ideas, clarification of concepts, and more in-depth discussion of the material. The use of the latest facilities and technology makes a major contribution to improving the quality of teaching. The use of multimedia, interactive classrooms, and online resources can enrich students' learning experiences.